Pixel-Based Parallel-Coordinates Technique For Outlier Detection In Cardiac Patient Dataset. - Hasimah, H.M.; Azuraliza, A.B.; Abdul Razak, H. (2007)
Visual Exploration technique applies human visual perception to explore large data sets and have proven to be of high value in exploratory data analysis. Pixel-based visual exploration relies on basic features that human perceptual system inherently assimilates very quickly: color size and shape.